Pendekatan Fraud Hexagon Theory Untuk Menganalisis Potensi Kecurangan Laporan Keuangan Perusahaan Sektor Keuangan Yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021 - Pasaribu, Ruth Christiana; Wiwik Hidajah Ekowati (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
This study aims to examine the fraud hexagon theory elements consisting of stimulus, opportunity, rationalization, capability, arrogance, and collusion to analyze potential financial statement fraud. The population of this study includes the entire financial sector companies listed on the Indonesia Stock Exchange from 2019 to 2021, from which 260 samples selected through purposive sampling method and tested by multiple regression method utilizing Statistical Product and Service Solution (SPSS) version 25 software. The findings of this study exhibited that stimulus, opportunity, rationalization, capability, arrogance, and collusion respectively assessed by financial target, ineffective internal company monitoring, auditor changes, director changes, frequent appearances of CEO photos, and market performance had a positive effect on potential financial statement fraud. Whilst, stimulus, opportunity, and collusion respectively assessed by financial stability and external pressure, independent auditor quality, and government projects had no effect on potential financial statement fraud